Understanding the Impact of School Safety on the High School Transition Experience: From Etiology to Prevention, Flint, Michigan, 2016 - Melde, Chris ([Verlag nicht ermittelbar], 2021)
This is a multi-method study of school violence and victimization during the transition to high school. This study has two major data collection efforts. First, a full population survey of 7th through 10th grade students across 10 Flint Community Schools (fall 2016) -- which serve primarily African American and poor populations -- that will identify patterns of student victimization, including the location and seriousness of violent events, and examine the connections between school and community violence. This will be followed by a three-wave panel qualitative study of 100 students interviewed every 6 months beginning in the spring of their 8th grade year (spring 2017) and continuing through their 9th grade year. The goal of the interviews will be to further the research from the survey and develop a deeper understanding of how school safety impacts the transition experience, school violence, including how communities conflict impacts school safety, and what youth do to protect themselves from school-related victimization. Researchers integrated crime incident data from the Flint police department as a source for triangulation of findings. A community workgroup will provide guided translation of findings generated from mixed-methods analyses, and develop an action plan to help students successfully transition to high school. Results and policy implications will be given to practitioner, researcher, and public audiences through written, oral, and web-based forums. De-identified data will be archived at the National Archive of Criminal Justice Data.